An Overview of 24 Years of Molecular Phylogenetic Studies in Phallales (Basidiomycota) With Notes on Systematics, Geographic Distribution, Lifestyle, and Edibility - Melanda, Gislaine C. S.; Silva-Filho, Alexandre G. S.; Lenz, Alexandre Rafael; Menolli, Nelson; Lima, Alexandro de Andrade de; Ferreira, Renato Juciano; Assis, Nathalia Mendonça de; Cabral, Tiara S.; Martín, María P.; Baseia, Iuri Goulart (Frontiers in Microbiology, 2021)
The order Phallales (Basidiomycota) is represented by gasteroid fungi with expanded and sequestrate basidiomata, known as stinkhorns and false truffles. In phalloids, the first DNA sequence was published in 1997 and, after that, some studies aimed to resolve phylogenetic conflicts and propose new species based on DNA markers; however, the number of families and genera in the order still generates controversies among researchers. Thus, this work aims to provide an overview of Phallales diversity represented by selected DNA markers available in public databases. We retrieved Phallales sequences from DNA databases (GenBank and UNITE) of seven markers (ITS, nuc-LSU, nuc-SSU, mt-SSU, ATP6, RPB2, and TEF1-α). To compose our final dataset, all ITS sequences retrieved were subjected to BLASTn searches to identify additional ITS sequences not classified as Phallales. Phylogenetic analyses based on Bayesian and Maximum Likelihood approaches using single and combined markers were conducted. All ITS sequences were clustered with a cutoff of 98% in order to maximize the number of species hypotheses. The geographic origin of sequences was retrieved, as well as additional information on species lifestyle and edibility. We obtained a total of 1,149 sequences, representing 664 individuals. Sequences of 41 individuals were unidentified at genus level and were assigned to five distinct families. We recognize seven families and 22 genera in Phallales, although the delimitation of some genera must be further revisited in order to recognize only monophyletic groups. Many inconsistencies in species identification are discussed and the positioning of genera in each family is shown. The clustering revealed 118 species hypotheses, meaning that approximately 20% of all described species in Phallales have DNA sequences available. Information related to geographic distribution represents 462 individuals distributed in 46 countries on all continents, except Antarctica. Most genera are saprotrophic with only one putative ectomycorrhizal genus, and 2.1% of the legitimate specific names recognized in Phallales are confirmed edible species. Great progress in the molecular analyses of phalloids has already been made over these years, but it is still necessary to solve some taxonomic inconsistencies, mainly at genus level, and generate new data to expand knowledge of the group.